Evaluación de dos porta-injertos en la producción vegetativa de plántulas de Tomate de Árbol (solanum betaceum cav.) eco tipo gigante anaranjado en el Cantón Ibarra, Provincia de Imbabura - Quillupangui Paucar, Pablo Enrique (2013)
This research was conducted in the county of Ibarra in the province of Imbabura, in order to determine the response of vegetative production by grafting onto the seedlings from the tomato fruit tree of two wild solanaceous rootstocks: tabaquillo (nicotiana glauca G.) and palo blanco (solanum auriculatum A.); a lso, to identify the rootstock which attains higher fruit production of tomato fruit seedlings and to analyze economically the treatments that were studied. We applied the randomized complete design (DCA), with five treatments and four repetitions. The variables were subjected to analysis of variance using the Tukey test at 5% and classified to determine statistical differences between the treatments. The following variables were evaluated: days to arrest, arrest rate, plant height, stem diameter, number of leaves per plant of tomato grafting at 60 days from planting, and economic analysis. It concluded: The rootstocks of tabaquillo and wild solanaceous palo blanco are compatible with the tomato tree and have different levels of tolerance to attack by nematodes in subtropical valley floors, the use of the types of grafts as vegetative propagation methods or asexual tree tomato were efficient in the percentage of engraftment generating a significant number seedlings with best features and good quality, the tabaquillo and palo blanco were the rootstocks with greater performance and lower incidence of nematode attack, the best propagation of tree tomato seedlings was achieved through vegetative production through the use of side and terminal end barb grafts with wild rootstocks tolerant to nematodes.